Glial Activation and Expression of the Serotonin Transporter in Chronic Fatigue Syndrome - Noda, Mami; Ifuku, Masataka; Hossain, Md. Shamim; Katafuchi, Toshihiko (Frontiers in Psychiatry, 2018)
Fatigue is commonly reported in a variety of illnesses and has major impact on quality of life. Chronic fatigue syndrome (CFS) is a debilitating syndrome of unknown etiology. The clinical symptoms include problems in neuroendocrine, autonomic, and immune systems. It is becoming clear that the brain is the central regulator of CFS. For example, neuroinflammation, especially induced by activation of microglia and astrocytes, may play a prominent role in the development of CFS, though little is known about molecular mechanisms. Many possible causes of CFS have been proposed. However, in this mini-review, we summarize evidence for a role for microglia and astrocytes in the onset and the maintenance of immunologically induced CFS. In a model using virus mimicking synthetic double-stranded RNA, infection causes sequential signaling such as increased blood brain barrier (BBB) permeability, microglia/macrophage activation through Toll-like receptor 3 (TLR3) signaling, secretion of IL-1, upregulation of the serotonin transporter (5-HTT) in astrocytes, reducing extracellular serotonin (5-HT) levels and hence reduced activation of 5-HT1A receptor subtype. Hopefully, drug discovery targeting these pathways may be effective for CFS therapy.